1996
DOI: 10.1111/j.1476-5381.1996.tb15730.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cyclic GMP‐dependent vasodilators on the expression of inducible nitric oxide synthase in vascular smooth muscle cells: role of cyclic AMP

Abstract: 1 In the present study we examined whether interleukin-lf (IL-Ifl) increases the activity of adenylyl cyclase in vascular smooth muscle cells and determined its role in the cytokine-induced expression of the inducible nitric oxide synthase (iNOS) and activation of nuclear transcription factor-KB (NF-KB). In addition the interaction between cyclic AMP-and cyclic GMP-elevating agonists on the IL-iIf-stimulated expression of iNOS was examined.2 Exposure of vascular smooth muscle cells to IL-,IB stimulated the for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
18
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 49 publications
5
18
0
Order By: Relevance
“…In addition to regulating expression, NO is also able to attenuate iNOS activity by destabilizing iNOS dimers through effects on the heme prosthetic group or by S-nitrosylating iNOS directly (35). In contrast to negative regulation of iNOS by NO, studies have also established that NO can augment iNOS expression (37)(38)(39). Our findings support a role for iNOS-derived NO in the amplification of iNOS levels in human cells.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…In addition to regulating expression, NO is also able to attenuate iNOS activity by destabilizing iNOS dimers through effects on the heme prosthetic group or by S-nitrosylating iNOS directly (35). In contrast to negative regulation of iNOS by NO, studies have also established that NO can augment iNOS expression (37)(38)(39). Our findings support a role for iNOS-derived NO in the amplification of iNOS levels in human cells.…”
Section: Discussionsupporting
confidence: 64%
“…iNOS-derived NO can also inhibit iNOS enzymatic function through post-translational modifications (35,36). In contrast to negative regulation, NO positively regulates iNOS expression in certain rodent cell types and in human cells, but the mechanisms by which this positive feedback occurs is poorly understood (37)(38)(39)(40).…”
mentioning
confidence: 99%
“…Although the human iNOS gene does not posses a sequence resembling the CRE consensus sequence [85], the influence of cAMP could still be an important factor in the transcriptional regulation of the iNOS gene [86]. Furthermore, the stimulatory action of cAMP does not appear to be related to the activation of NF-ĸB which is a nuclear transcription factor for iNOS [46, 87]. …”
Section: Role Of the Natriuretic Peptides And Their Receptors In Modumentioning
confidence: 99%
“…A recent study with mesangial cells suggested that NO-cGMP and cGMP analogues contribute to iNOS induction and its downregulation (Pérez-Sala et al, 2001). Though many other studies have presented the up or downregulation of iNOS expression by NO, these studies did not identify the cGMP-dependency of such regulations (Park et al, 1994;Mühl and Pfeilschifter, 1995;Boese et al, 1996;Park et al, 1997). Studies on iNOS expression have also shown different results with respect to up and downregulation.…”
Section: Discussionmentioning
confidence: 89%